Surveying the practice of strategic planning for school excellence : a fast-track to the peak - Ayodele, Lasisi Abbas; Mohd Ali, Hairuddin (Lambert Academic Publishing, 2012)

(untitled)
Strategic planning strives to give prospect to institutional stakeholders and administrators to tackle the internal and external challenges for school excellence. This book is inevitable for researchers, school administrators, students and other people who wish to establish educational institutions. This book enhances the school owners to reach the peak and guides both administrators as well as stakeholders to set standard school strategic plan on fast track for excellent achievement.